Optical cavity efficacy and lasing of focused ion beam milled GaN/InGaN micropillars - El-Ella, H; Collins, D; Kappers, M; Taylor, R; Oliver, R (2012)
Focused ion beam milled micropillars employing upper and lower distributed Bragg reflectors (DBRs) and incorporating InGaN quantum dots were analysed both microstructurally and optically. Comparison of the surface characteristics and the optical resonance of pillars milled employing two recipes, using comparatively higher and lower beam currents, were carried out through electron back scatter diffraction, atomic force microscopy and low temperature micro-photoluminescence. Low temperature micro-photoluminescence highlighted singly resolved InGaN quantum dot emission as well as modes with typical quality factors (Q) of ∼200-450 for typical 1-4μm diameter pillars, while one exceptional 4μm diameter pillar displayed optically-pumped lasing with a Q of ∼1100 at a threshold of ∼620 kWcm-2. The higher current recipe resulted in pillars with thicker surface amorphous layers, while the lower current recipe resulted in pillars with thinner surface amorphous layers but rougher surfaces. Micropillars milled through the recipe utilising higher beam currents were tentatively shown to possess lower Qs on average, correlating with the thickness of the surface amorphous layer. Finite difference frequency domain simulations in combination with analytical approximations of the various optical loss pathways suggested that surface scattering related optical loss was not significant compared to internal-based and surface absorption-based losses. The magnitude of the internal loss was observed to fluctuate significantly, which was thought to relate to the fluctuating micro-structure within the lower DBR and within the InGaN quantum dot layer. © 2012 American Institute of Physics.